2021
DOI: 10.14309/ajg.0000000000001366
|View full text |Cite|
|
Sign up to set email alerts
|

Pain Experience in Pancreatitis: Strong Association of Genetic Risk Loci for Anxiety and PTSD in Patients With Severe, Constant, and Constant-Severe Pain

Abstract: INTRODUCTION: Recurrent acute pancreatitis (RAP) and chronic pancreatitis (CP) are progressive inflammatory syndromes with variable features. Pain is the primary feature that contributes to low physical and mental quality of life with a third of patients reporting severe pain. Pain experience is worsened by depression. Here, we tested the hypothesis that genetic risk of the psychiatric conditions of anxiety and post-traumatic stress disorder (PTSD) is associated with pain in CP and RAP + CP subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Most other conditions strongly associated with AP and CP are either symptoms (R10.X), treatments (Y83.6), complications (N17.9), or sequela (E10, E11) of the conditions. Recent studies from the NAPS2 ( 45 , 46 ) and multicenter CP pain study ( 47 ) cohorts demonstrated a strong association with depression and anxiety in patients with pancreatitis, especially those with pain. A striking but not surprising finding was the relative high risk of intentional self-harm ( ICD-10 X60-X65 family; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Most other conditions strongly associated with AP and CP are either symptoms (R10.X), treatments (Y83.6), complications (N17.9), or sequela (E10, E11) of the conditions. Recent studies from the NAPS2 ( 45 , 46 ) and multicenter CP pain study ( 47 ) cohorts demonstrated a strong association with depression and anxiety in patients with pancreatitis, especially those with pain. A striking but not surprising finding was the relative high risk of intentional self-harm ( ICD-10 X60-X65 family; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We thank Liu et al for their letter in reference to our recent paper by Dunbar et al (1,2). We will address the 4 points sequentially.Cohort numbers vary between comparisons.…”
mentioning
confidence: 85%
“…To further clarify the first contention, see the “Variables” subsection of our “Methods” section in our paper (1) where we specify that we are using the same pool of patients with pancreatitis from the NAPS2 in 2 groups to account for similarities between CP and RAP. Similarly, we did group patients by pain category in such a way that some patients may overlap between the groups (see “Pain categories and quality of life” (1)). However, we do not believe that the genetic association seen with CTNND2 across all 3 pain categories is only due to an association with constant-severe pain.…”
mentioning
confidence: 99%
“…In this issue of The American Journal of Gastroenterology , Dunbar et al (22) evaluated patients with CP and recurrent acute pancreatitis (RAP) from the North American Pancreatitis Study II (NAPS2) to determine whether there are associations between pain and SNPs related to anxiety and/or PTSD. The patients were classified into 3 pain phenotypes categories: constant, severe, and constant-severe pain.…”
mentioning
confidence: 99%